STRATEGI PEMBELAJARAN ADAPTIF GURU PAI DALAM MENGHADAPI KEBERAGAMAN TINGKAH LAKU SISWA PADA MATA PELAJARAN PAI DI SMP - Alfin Febriansah; Muh. Hanif (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2026)
The diversity of students’ behavior in Islamic Religious Education requires teachers to apply flexible teaching strategies that suit classroom conditions. This study aims to describe the adaptive learning strategies used by an Islamic Religious Education teacher in dealing with differences in students’ character, abilities, and classroom responses at the junior high school level. This research employed a descriptive qualitative approach, with data collected through an in-depth interview with one Islamic Religious Education teacher as the main informant. The findings show that the teacher applied adaptive strategies by using the teaching module as a guide, selecting methods based on the learning material, assigning tasks according to students’ abilities, and applying a personal approach to students who needed more attention. The teacher also used digital media, such as smartphones and Canva, under supervision to attract students’ attention and maintain their engagement in learning. In addition, the morning Qur’an reading routine served as part of the school’s religious reinforcement. These adaptive strategies indicate that Islamic Religious Education is not only concerned with delivering material but also with the teacher’s ability to understand students’ conditions and guide their behavior in a humanistic way. Keywords: Teaching Flexibility, Personal Approach, Religious Habituation. Abstrak Keberagaman tingkah laku siswa dalam pembelajaran Pendidikan Agama Islam menuntut guru untuk memiliki cara mengajar yang fleksibel dan sesuai dengan kondisi kelas. Penelitian ini bertujuan untuk mendeskripsikan strategi pembelajaran adaptif guru PAI dalam menghadapi perbedaan karakter, kemampuan, dan respons siswa pada mata pelajaran PAI di SMP. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik wawancara mendalam kepada seorang guru PAI sebagai informan utama. Hasil penelitian menunjukkan bahwa guru PAI menerapkan strategi adaptif melalui penggunaan modul ajar sebagai pedoman, pemilihan metode sesuai materi, pemberian tugas sesuai kemampuan siswa, serta pendekatan personal kepada siswa yang membutuhkan perhatian lebih. Guru juga memanfaatkan media digital seperti HP dan Canva secara terbimbing untuk menarik perhatian siswa dan menjaga keterlibatan mereka dalam pembelajaran. Selain itu, pembiasaan membaca Al-Qur’an pada pagi hari menjadi bagian dari penguatan keagamaan di sekolah. Strategi adaptif ini menunjukkan bahwa pembelajaran PAI tidak hanya berfokus pada penyampaian materi, tetapi juga pada kemampuan guru memahami kondisi siswa dan membina perilaku mereka secara humanis.